A Behavioral Study of Pakistani Library and Information Science Community on Facebook - Sehrish Ali, Pervaiz Ahmed (IJoLIS, 2024)
Purpose: To explore how Pakistani LIS community interact with each other, especially their behaviour on Facebook. The reason behind this research was researchr's general but sporadic observation that community'sonline behavour was volatile.